Metagenomic Analysis of Microbial Composition Revealed Cross-Contamination Pathway of Bacteria at a Foodservice Facility - Lim, Eun Seob; Kim, Jin Ju; Sul, Woo Jun; Kim, Joo-Sung; Kim, Bomin; Kim, Hun; Koo, Ok Kyung (Frontiers in Microbiology, 2021)
Bacterial contamination of food-contact surfaces can be a potential risk factor for food quality and safety. To evaluate the spatial and temporal variations of the potential cross-contamination routes, we conducted a biogeographical assessment of bacteria in a foodservice facility based on the diversity of microflora on each surface. To this end, we performed high-throughput amplicon sequencing of 13 food-contact and non-food contact surfaces in a foodservice facility throughout a year. The results showed that Bacillus, Acinetobacter, Streptophyta, Enterobacter, Pseudomonas, Serratia, Enhydrobacter, Staphylococcus, Paracoccus, and Lysinibacillus were the dominant genera found on the kitchen surfaces of the foodservice facility. Depending on the season, changes in Firmicute/Proteobacteria ratios were observed, and the fan becomes the main source of outdoor air contamination. The microbial flow associated with spoilage was also observed throughout food preparation. Taken together, our results would be a powerful reference to hygiene managers for improvement of food processes.